Physical, mechanical, and biological properties of electrophoretically deposited lithium-doped calcium phosphates. Issue 3 (15th February 2018) - Drdlik, Daniel; Slama, Martin; Hadraba, Hynek; Drdlikova, Katarina; Cihlar, Jaroslav
Abstract: In the present work, the preparation of sintered lithium-doped tricalcium phosphates was studied, along with their physical, mechanical, and biological properties. Calcium phosphates were shaped via the use of electrophoretic deposition (EPD), using colloidally milled dispersions of hydroxyapatite (HAp) particles. The dispersions were stabilised with monochloroacetic acid. Lithium was incorporated into the structure via an addition of lithium chloride, which also served to optimise the deposition process. The dispersions were milled colloidally for periods of 0–48 h. The colloidal milling resulted in two effects: i) disintegration of the commercial HAp powder (10 µm) agglomerates, ii) unimodal distribution of the HAp particles ( 170 nm). The fine particles of the milled HAp dispersions accelerated the deposition rate, and increased the mass of the deposit. The reduced size of the initial particles, owed to the milling, led to the superior arrangement of the particles during deposition and to reduced porosity after sintering (1050–1250 °C). The HAp decomposed into tricalcium phosphate phases during sintering. At a sintering temperature of 1250 °C, grain growth occurred, which consequently resulted in a slight degradation of the mechanical properties (reduction in hardness and Young's modulus). In contrast, the hardness and Young's modulus increased as the dispersion milling time increased (smaller grain size after sintering); however, the fracture toughness did not change. The results of the biological testing confirmed the bioactivity of the material through the growth of the apatite layer in the simulated body fluid (SBF), and the biodegradation of the prepared materials in the Tris-HCl solution. With regard to the preparation of compact lithium-doped tricalcium phosphates, the best results were obtained in the case of the sample that utilised the dispersion that was milled for 48 h, and was sintered at 1050 °C.